2019
DOI: 10.1002/path.5228
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput sequencing identifies aetiology‐dependent differences in ductular reaction in human chronic liver disease

Abstract: Ductular reaction (DR) represents the activation of hepatic progenitor cells (HPCs) and has been associated with features of advanced chronic liver disease; yet it is not clear whether these cells contribute to disease progression and how the composition of their micro‐environment differs depending on the aetiology. This study aimed to identify HPC‐associated signalling pathways relevant in different chronic liver diseases using a high‐throughput sequencing approach. DR/HPCs were isolated using laser microdiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…Indeed, in different pathologic settings, they have been shown to originate from reactive cholangiocytes, hepatic and biliary progenitor/stem cells (HPCs), or transdifferentiated hepatocytes/hybrid hepatocytes (sex‐determining region Y‐box 9–positive [Sox9 + ] hepatocyte nuclear factor 4 alpha–positive) . This heterogeneity has rendered the identification of common, specific markers of DRCs quite challenging as different DRCs can express different markers depending on their origin and the nature of the injury . On the other hand, frequently used markers to identify DRCs, such as epithelial cell adhesion molecule, SOX9, and cytokeratins 7 and 19, lack specificity as they are not exclusively expressed by DRCs but also by normal cholangiocytes and, in some cases, SCs.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in different pathologic settings, they have been shown to originate from reactive cholangiocytes, hepatic and biliary progenitor/stem cells (HPCs), or transdifferentiated hepatocytes/hybrid hepatocytes (sex‐determining region Y‐box 9–positive [Sox9 + ] hepatocyte nuclear factor 4 alpha–positive) . This heterogeneity has rendered the identification of common, specific markers of DRCs quite challenging as different DRCs can express different markers depending on their origin and the nature of the injury . On the other hand, frequently used markers to identify DRCs, such as epithelial cell adhesion molecule, SOX9, and cytokeratins 7 and 19, lack specificity as they are not exclusively expressed by DRCs but also by normal cholangiocytes and, in some cases, SCs.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…This etiology‐dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus–infected and PSC livers as models for hepatocellular or biliary injury, respectively. The study identified significant differences in the expression of over 300 genes between the DRCs of the two diseases and defined how these differences influence the recruiting and homing of inflammatory cells …”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…The contribution of the ductular reactions (DRs) to liver regeneration has been more problematic – a scenario described by Govaere et al in a recent issue of The Journal of Pathology . Many models of murine liver injury have targeted either the biliary epithelium or hepatocytes, but genetic lineage tracing has found that most of this regeneration was accomplished through hepatocyte replication, even though DRs were very prominent.…”
mentioning
confidence: 99%
“…The validation cohort of 56 formalin‐fixed paraffin‐embedded (FFPE) samples had equal numbers of HCV and PSC cases with 10 being early stage fibrosis (F0–F1) and 18 being advanced stage (F3–F4) for each disease. When comparing HPCs with their neighbouring hepatocytes, RNA‐seq identified 2451 genes in HCV and 1696 genes in PSC that were differentially expressed .…”
mentioning
confidence: 99%
See 1 more Smart Citation